2019
DOI: 10.1038/s41598-019-49869-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reversal in perpendicularly magnetized antidot arrays with intrinsic and extrinsic defects

Abstract: Defects can significantly affect performance of nanopatterned magnetic devices, therefore their influence on the material properties has to be understood well before the material is used in technological applications. However, this is experimentally challenging due to the inability of the control of defect characteristics in a reproducible manner. Here, we construct a micromagnetic model, which accounts for intrinsic and extrinsic defects associated with the polycrystalline nature of the material and with corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…1 for the procedure used). We show that the trained system can estimate not only the DM exchange constant, which is in good agreement with experiments, but also the distribution of the magnetic anisotropy energy, for which only a few experimental studies have been reported thus far 31,32 .…”
Section: Introductionsupporting
confidence: 80%
“…1 for the procedure used). We show that the trained system can estimate not only the DM exchange constant, which is in good agreement with experiments, but also the distribution of the magnetic anisotropy energy, for which only a few experimental studies have been reported thus far 31,32 .…”
Section: Introductionsupporting
confidence: 80%
“…The degradation of MR for the larger antidots suggests that the edge effects at the nanostructure boundaries play important role in scattering of charge carriers, and thus modify the magnetotransport characteristics. It is well known that impurities, disorder and additional phases emerging at antidot edges can significantly change magnetic and electronic properties of the percolated thin films [ 44 , 45 , 46 , 47 , 48 ], and similar mechanism is expected in the studied Bi antidot arrays. On the other hand, Bergman, Tornow et al [ 23 , 49 , 50 ] showed that magnetoresistance changes can be also understood by considering current distortions which appear around inclusions or voids in the host material.…”
Section: Resultsmentioning
confidence: 74%
“…In the same way, when the magnetic pulse is applied perpendicular to the hole axis, one of the three resonance modes disappears. Notice that, although our study was performed in an ideal system with no edge roughness, the inclusion of such defects should modify both the shape and the number of resonance modes 25,31,56,58,79 . Although, we expect that due to the significant increase of the unidirectional anisotropy, the changes due to the extrinsic defects are minor or despicable.…”
Section: Discussionmentioning
confidence: 99%
“…From the experimental point of view there are several techniques for obtaining magnetic antidot arrays such as e-beam 2 , 17 , UV 18 and colloidal 19 lithography, porous anodic alumina 20 , 21 , block copolymer templates 22 , nanochannel glass 23 and focused ion beam (FIB) patterning 24 26 , among others. Regarding the features that antidots possess, it has been widely reported that static properties such as remanence 27 , coercivity 27 , 28 , and the easy-axis magnetic anisotropy 28 31 , can be controlled by modifying the hole size, the distance between them, and the material used to fabricate the array. Therefore, the appearance of different domain structures, magnetoresistance effects, distinct magnetization reversal processes and modifications on the equilibrium magnetic configurations when changing the shape, size, and density of antidot holes have been deeply studied 17 , 32 36 .…”
Section: Introductionmentioning
confidence: 99%